Attempt at taxonomical characterization of some Rhizobial species by intact cell MALDI mass spectrometry - Prabhu, R. R.; Kulkarni, Mahesh J.; Parasharami, V. A.; Santhakumari, B.; Paranjape, S. (World Journal of Microbiology & Biotechnology, 2007)
In the present study an attempt was made to exploit the benefit of intact cell MALDI mass spectrometry (ICM-MS) in bringing out similarities and differences among some Rhizobium species and a species of Agrobacterium based on specific mass:charge (m/z) values. Rhizobium species isolated from the root nodules of selected leguminous plants were analysed by ICM-MS. The spectra were acquired in the range of 500-10,000 Da yielding several peaks specific to each species. The peaks obtained corresponded to the respective bacterial cell surface molecules which were desorbed during matrix-assisted laser desorption ionization. The number of peaks were more in the range of 500-1200 Da. Dice similarity coefficient analysis of m/z values indicated that Rhizobium species isolated from Trigonella foenum-graecum and Pisum arvense showed more similarity than any other species. Agrobacterium species did show a few common m/z values in comparison with other Rhizobium species. This clearly shows that Agrobacterium is closely related to Rhizobium. Eventually, ICM-MS technique offers clear, distinct, and consistent results for replicates, in less than an hour's time, therefore this technique has high potential in molecular taxonomy.
Keywords: ICM-MS; legume; molecular taxonomy; Rhizobium; symbiotic

Synthesis of 2-[4-(10H-Substituted Phenothiazine-3-yl)-6-Pyrimidin-2-Phenylthiol/ol/amine/thiol] Pyrroles - Narule, Meghasham; Meshram, Jyotsna S.; Santhakumari, B.; Shanware, A. (E-Journal of Chemistry, 2007)
2-[4-Hydroxy benz-1(propene-1-one)]Pyrrole II on treatment with phenyl thiourea, guanidine carbonate, urea and thiourea in alcoholic KOH yielded compounds III, IV, V, VI which on treatment with different aryl anilines gave compounds VII, VIII, IX, X which under goes cyclisation with sulphur and iodine to give 2-[4-(10H-substituted phenothiazine-3-yl)-6-pyrimidin-2-phenylthiol/-ol/-amine/-thiol] pyrrole XI(a-j), XII(a-j), XIII(a-j) and XIV(a-j) respectively. The structural products were characterized by elemental analysis and spectral data.

Identification of ripening specific proteins in tomato by intact tissue MALDI-TOF-MS. - Korwar, Arvind M.; Santhakumari, B.; Kulkarni, Mahesh J. (Electronic Journal of Food and Plants Chemistry, 2008)

Application of a stability-indicating thin-layer chromatographic method to the determination of tenatoprazole in pharmaceutical dosage forms - Dhaneshwar, Sunil R.; Bhusari, Vidhya K.; Mahadik, Mahadeo V.; Santhakumari, B. (Journal of AOAC International, 2009)
A sensitive, selective, precise, and stability-indicating thin-layer chromatographic (TLC) method was developed and validated for the determination of tenatoprazole both as a bulk drug and in formulation. The method uses TLC aluminum plates precoated with Silica Gel 60(F-254) as the stationary phase and the solvent system toluene-ethyl acetate-methanol (6 + 4 + 1, v/v/v). This system gave compact spots for tenatoprazole (R(f) value of 0.34 +/- 0.02). Tenatoprazole was subjected to acid and alkali hydrolysis, oxidation, and photodegradation. The peaks of the degradation products were well-resolved from that of the pure drug and had significantly different Rf values. Densitometric analysis of tenatoprazole was performed in the absorbance mode at 306 nm. The linear regression analysis data for the calibration plots showed a good linear relationship over the concentration range of 100-1500 ng/spot. The mean values of the correlation coefficient, slope, and intercept were 0.9989 +/- 1.42, 10.27 +/- 0.965, and 4894.2 +/- 1.24, respectively. The method was validated for precision, robustness, and recovery. The limit of detection and limit of quantitation were 50 and 100 ng/spot, respectively. Statistical analysis showed that the method is repeatable and selective for estimation of tenatoprazole. Because the method can separate the drug from its degradation products, it can be used to monitor stability.

Production, purification, and characterization of taxol and 10-DABIII from a new endophytic fungus gliocladium sp isolated from the Indian yew tree, taxus baccata - Sreekanth, D.; Syed, A.; Sarkar, S.; Sarkar, Dhiman; Santhakumari, B.; Ahmad, Absar; Khan, Mohammad Islam (Journal of Microbiology and Biotechnology, 2009)
We have isolated endophytic fungi from the Indian yew tree, Taxus baccata, and then screened for taxol production. Out of the 40 fungal cultures screened, one fungus Gliocladium sp. was found to produce taxol and 10-DABIII (10-deacetyl baccatin III). These compounds were purified by TLC and HPLC and characterized using UV-spectroscopy, ESI-MS, MS/MS, and proton NMR. One liter of Gliocladium sp. culture yielded 10 mu g of taxol and 65 mu g of 10-DABIII. The purified taxol from the fungus showed cytotoxicity towards cancer lines HL-60 (leukemia), A431 (epidermal carcinoma), and MCF-7 (breast cancer).
Keywords: 10 DAB III; Endophytic fungi; Gliocladium sp.; Taxol; Taxus baccata

Bioanalytical method development and validation of levalbuterol a β2-adrenergic agonist by RP-HPLC method - Ghemud, A. S.; Santhakumari, B.; Pharne, A. B.; Jadhav, M. M.; Jain, K. S.; Kulkarni, Mahesh J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)

Bioanalytical method development and validation of vildagliptin a novel dipeptidyl peptidase IV inhibitor by RP-HPLC method - Pharne, A. B.; Santhakumari, B.; Ghemud, A. S.; Jain, H. K.; Kulkarni, Mahesh J. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)
A simple, selective, rapid, precise and economical Reverse-Phase HPLC method has been developed and validated for quantitative determination of vildagliptin in plasma. Vildagliptin is a potent dipeptidyl peptidase IV inhibitor used for treatment of diabetes. Tolbutamide is used as an internal standard. The method was carried out with UV Spectrophotometric detection using a Perkin Elmer Series 200 HPLC system equipped with XBridge Shield C18 column (3.5 μm, 4.6x150mm) and a guard column of the same type, at a flow rate of 1.0mL/min. Detection was carried out at 210 nm. The mobile phase consisted of 50mM ammonium bicarbonate (pH 7.8) (solvent A) and acetonitrile (solvent B). The retention times of vildagliptin and tolbutamide were 11.2 min and 13.4 min respectively. The method was developed and tested for linearity range of 10μg/ml to 120μg/ml. The developed method was validated in terms of selectivity, accuracy, precision, linearity, and stability study. The proposed method uses less biological material and the method is MS compatible also. Method can be applicable for pharmacokinetic studies using HPLC or LC-MS.

Development and validation of a simple and sensitive RP-HPLC method for simultaneous estimation of drospirenone and ethinylestradiol in combined tablet dosage form - Warkad, Shrikant D.; Santhakumari, B.; Chandewar, A. V. (International Journal of Pharmacy and Pharmaceutical Sciences, 2012)

Development and validation of a sensitive bioanalytical method for the determination of sumatriptan in rat plasma by UPLC-MS - Kumbhar, Amruta B.; Galgatte, Upendra C.; Warkad, Shrikant D.; Santhakumari, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2013)

Analytical and bioanalytical UHPLC-MS method validation for determination of metformin, a bigunaide and sitagliptin, a DPP-4 inhibitor - Nakrani, Mital; Bairagee, Deepika; Goyal, Pradeep; Santhakumari, B. (International Journal of Pharmacy and Pharmaceutical Sciences, 2015)

Investigation of antiglycation activity of isoprenaline - Kolekar, Yogesh M.; Vannuruswamy, Garikapati; Bansode, Sneha B.; Santhakumari, B.; Thulasiram, Hirekodathakallu V.; Kulkarni, Mahesh J. (RSC Advances, 2015)
Advanced glycation end products (AGEs) are implicated in pathogenesis of diabetes and its complications. In this study, we report the ability of isoprenaline to inhibit the AGE modification of protein by fluorescence spectroscopy and western blotting. Isoprenaline was more effective in inhibiting AGE modification than aminoguanidine, a well known glycation inhibitor. Further, we show that isoprenaline inhibits at Amadori product formation during glycation reaction by various techniques such as MALDI-TOF-MS, LC-MS/MS, and fructosamine assay. Mass spectrometric analysis of the glycation reaction mixture incubated with isoprenaline suggested that it forms adducts with glucose and thus inhibits glycation. The finding of the additional property of isoprenaline of inhibiting glycation suggests that it is a potential candidate for drug repositioning for the treatment of diabetes and its complications, as it is an FDA approved drug.

Biosurfactant as a promoter of methane hydrate formation: thermodynamic and kinetic studies - Arora, Amit; Cameotra, Swaranjit Singh; Kumar, Rajnish; Balomajumder, Chandrajit; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Scientific Reports, 2016)
Natural gas hydrates (NGHs) are solid non-stoichiometric compounds often regarded as a next generation energy source. Successful commercialization of NGH is curtailed by lack of efficient and safe technology for generation, dissociation, storage and transportation. The present work studied the influence of environment compatible biosurfactant on gas hydrate formation. Biosurfactant was produced by Pseudomonas aeruginosa strain A11 and was characterized as rhamnolipids. Purified rhamnolipids reduced the surface tension of water from 72 mN/m to 36 mN/m with Critical Micelle Concentration (CMC) of 70 mg/l. Use of 1000 ppm rhamnolipids solution in C type silica gel bed system increased methane hydrate formation rate by 42.97% and reduced the induction time of hydrate formation by 22.63% as compared to water saturated C type silica gel. Presence of rhamnolipids also shifted methane hydrate formation temperature to higher values relative to the system without biosurfactant. Results from thermodynamic and kinetic studies suggest that rhamnolipids can be applied as environment friendly methane hydrate promoter.

Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine by heptavalent manganese at environmentally relevant pH - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The rapid increase in the population across the world has increased the consumption of pharmaceutical substances. These pharmaceutical substances have penetrated into the water through various ways. Mechanistic and spectroscopic investigations of Ru3+-catalyzed oxidative degradation of azidothymidine (AZT) by heptavalent manganese was studied for the first time. The values of pH-dependent apparent second-order rate constant show that Ru3+ accelerates the rate of the oxidative degradation of AZT by heptavalent manganese eight times faster than uncatalyzed reaction. Ru3+ catalytic oxidative degradation of AZT by heptavalent manganese was greatly depending on the pH. The removal of the AZT by heptavalent manganese in the presence of Ru3+ shows unit order with respect to heptavalent manganese, Ru3+, and AZT. The influences of dielectric constant, ionic strength, pH, addition of monomer, variation in catalyst concentration, etc. on the rate of the reaction were studied thoroughly and discussed in detail. The eight different products produced during the reaction were analyzed using the high-resolution mass spectrometry. Activation parameters were determined from variation in temperature during the reaction. The catalytic plausible mechanism was projected in which Ru3+ is oxidized to higher oxidation states of ruthenium by heptavalent manganese at environmentally relevant pH.
Keywords: Azidothymidine; catalysis; Degradation; Heptavalent manganese; kinetics; Mechanism

Oxidation of linezolid by permanganate in acidic medium: Pd(II) catalysis, kinetics and pathways - Kulkarni, Raviraj M.; Hanagadakar, Manjunath S.; Malladi, Ramesh S.; Santhakumari, B.; Nandibewoor, Sharanappa T. (Progress in Reaction Kinetics and Mechanism, 2016)
The uncatalysed and Pd(II)-catalysed oxidation of linezolid (LNZ) by permanganate (PMGT) in acidic medium was carried out in the pH range from 3.0 to 6.0. The second order rate constants were found to decrease with increase in pH. The apparent second order rate constants for the uncatalysed reaction were, for example, k `'(app)= 6.32 dm(3) mol(-1) at pH 3.0 and k `'(app). = 2.64 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C and for the Pd(II)-catalysed reaction the total apparent second order rate constants were k `'(app) = 75.5 dm(3) mol(-1) s(-1) at pH 3.0 and k `'(app). = 45.66 dm(3) mol(-1) s(-1) at pH 6.0 and at 25 +/- 0.2 degrees C. The rate constant of the Pd(II)-catalysed reaction was thus ten times higher than for the uncatalysed reaction. The oxidation products of the reaction were identified using high resolution LC-MS. The reaction progresses via formation of a Pd-LNZ complex, which reacts with acidic PMGT to form an intermediate compound, which then decomposes to give oxidised products. The dependence of the rate of reaction on various parameters, such as pH, temperature, [LNZ], [PMGT], [Pd(II)], dielectric constant and ionic strength were studied and activation parameters for the reaction were evaluated and discussed.

Oxidative transformation of antiretroviral drug zidovudine during water treatment with permanganate: reaction kinetics and pathways - Kulkarni, Raviraj M.; Bhamare, Vijaykumar S.; Santhakumari, B. (Desalination and Water Treatment, 2016)
The presence of the pharmaceutical substances in the water has been reported by many studies and has attracted attention across the world. The mechanistic insight into oxidation of antiretroviral drug zidovudine (ZDV) by potassium permanganate was investigated between the pH values 3.0 and 9.0. The pH-dependent second-order rate constants were determined and rate constants decreased with an increase in pH. The products of the reaction were identified by high-resolution mass spectrometry. A probable mechanism is proposed which involves the formation of an intermediate complex between permanganate and ZDV, which further undergoes degradation in subsequent fast steps to form various oxidized products. The different parameters like effect of initially added products, solvent polarity, ionic strength, temperature, and pH on the rate of the oxidative degradation of ZDV by permanganate were systematically studied. The various activation parameters were determined from the effect of variation in temperature on the oxidative degradation of ZDV by permanganate in acidic medium and discussed in detail.
Keywords: Degradation; kinetics; Mechanism; Permanganate; Zidovudine

Ru-TiO2 semiconducting nanoparticles for the photo-catalytic degradation of bromothymol blue - Kulkarni, R. M.; Malladi, R. S.; Hanagadakar, M. S.; Doddamani, M. R.; Santhakumari, B.; Kulkarni, S. D. (Journal of Materials Science-Materials in Electronics, 2016)
Photo-catalytic degradation of bromothymol blue (BTB) in an aqueous medium by Ru-TiO2 using UVC (254 nm) irradiation was investigated for a pH range of 4.0-8.0. The liquid impregnation method was used to synthesize 0.2, 0.4 and 0.8 % ruthenium doped TiO2 (Ru-TiO2) nanoparticles. The characterizations of resulting nanoparticles were done using X-ray diffraction, scanning electron microscopy, fourier transform infrared spectroscopy, transmission electron microscopy (TEM) and energy dispersive X-ray spectroscopy analysis. The crystallite sizes of doped and undoped nanoparticles were determined from X-ray diffraction spectra using Scherrer equation. The average crystallite size of undoped TiO2 was found to be 17.00 nm, whereas the crystallite sizes of 0.2, 0.4 and 0.8 % Ru-TiO2 were 16.67, 15.70 and 14.40 nm respectively. The TEM images confirm the particle sizes to be 10-40 nm. Pseudo-first order rate constants (k(obs)) determined were found to decrease with increase in pH. The effect of BTB Concentration, catalyst dosage, a percentage of doping of photo catalyst, pH and UV light intensity of BTB on the degradation rate were also examined.

Serum responsive proteome reveals correlation between oxidative phosphorylation and morphogenesis in Candida albicans ATCC10231 - Ahmed, Radfan; Kodgire, Santosh; Santhakumari, B.; Patil, Rajendra; Kulkarni, Mahesh J.; Zore, Gajanan (Journal of Proteomics, 2018)
To understand the impact of fetal bovine serum (FBS) on metabolism and cellular architecture in addition to morphogenesis, we have identified FBS responsive proteome of Candida albicans. FBS induced 34% hyphae and 60% pseudohyphae in C. albicans at 30 C while 98% hyphae at 37 C. LC-MS/MS analysis revealed that 285 proteins modulated significantly in response to FBS at 30 degrees C and 37 degrees C. Out of which 152 were upregulated and 62 were downregulated at 30 degrees C while 18 were up and 53 were downregulated at 37 degrees C. Functional annotation suggests that FBS may inhibit glycolysis and fermentative pathway and enhance oxidative phosphorylation (OxPhos), TCA cycle, amino acid and fatty acid metabolism indicating a use of alternative energy source by C. albicans. OxPhos inhibition assay using sodium azide corroborated the correlation between inhibition of glycolysis and enhanced OxPhos with pseudohyphae formation. C. albicans induced hyphae in response to FBS irrespective of down regulation of Rasl,Asrl/Asr2, indicates the possible involvement of MAPK and cAMP-PKA independent pathway. The Cell wall of cells grown in presence of FBS at 30 degrees C was rich in mannan, Beta 1,3glucan and chitin while membranes were rich in ergosterol compared to those grown at 37 degrees C. Significance of the study: This is the first study suggesting a correlation between OxPhos and morphogenesis especially pseudohyphae formation in C. albicans. Our data also indicate that fetal bovine serum (FBS) induced morphogenesis is multifactorial and may involve MAPK and cAMP-PKA independent pathway. In addition to morphogenesis, our study provides an insight in to the modulation of metabolism and cellular architecture of C. albicans in response to FBS.
Keywords: analysis; Candida albicans; Fetal bovin serum; Liquid chromatography mass spectrometry; morphogenesis; Oxidative phosphorylation; pathogenicity

Streptomyces sp metabolite(s) promotes Bax mediated intrinsic apoptosis and autophagy involving inhibition of mTOR pathway in cervical cancer cell lines - Dan, Vipin Mohan; Muralikrishnan, Balaji; Sanawar, Rahul; Vinodh, J. S.; Burkul, Bhushan Bapusaheb; Srinivas, Kalanghad Puthankalam; Lekshmi, Asha; Pradeep, N. S.; Dastager, Syed G.; Santhakumari, B.; Santhoshkumar, Thankayyan R.; Kumar, R. Ajay; et al. (Scientific Reports, 2018)
In cervical cancer, the association between HPV infection and dysregulation of phosphoinositide 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway (PI3K/AKT/mTOR pathway) places mTOR as an attractive therapeutic target. The failure of current treatment modalities in advanced stages of this cancer and drawbacks of already available mTOR inhibitors demand for novel drug candidates. In the present study we identified the presence of a mTOR inhibitor in an active fraction of the ethyl acetate extract of Streptomyces sp OA293. The metabolites(s) in the active fraction completely inhibited mTORC1 and thereby suppressed activation of both of its downstream targets, 4E-BP1 and P70S6k, in cervical cancer cells. In addition, it also stalled Akt activation via inhibition of mTORC2. The mechanism of mTOR inhibition detailed in our study overcomes significant drawbacks of well known mTOR inhibitors such as rapamycin and rapalogs. The active fraction induced autophagy and Bax mediated apoptosis suggesting that mTOR inhibition resulted in programmed cell death of cancer cells. The molecular weight determination of the components in active fraction confirmed the absence of any previously known natural mTOR inhibitor. This is the first report of complete mTOR complex inhibition by a product derived from microbial source.

Bioactivities and molecular networking-based elucidation of metabolites of potent actinobacterial strains isolated from the Unkeshwar geothermal springs in India - Mehetre, Gajanan T.; Vinodh, J. S.; Burkul, Bhushan B.; Desai, D.; Santhakumari, B.; Dharne, Mahesh S.; Dastager, Syed G (RSC Advances, 2019)
The bioactive potential of Actinobacteria endemic to hot springs has rarely been investigated. This study highlights the cultivable diversity and bioactivities of Actinobacteria associated with the Unkeshwar hot springs, India. Potent strains were evaluated for their biosynthetic potentials and metabolite analysis was performed using effective dereplication molecular networking tools. A total of 86 actinobacterial strains were isolated and grouped into 21 distinct genera, based on 16S rRNA gene sequence analysis. These strains included rare members such as Micromonospora, Marmoricola, Actinomadura, Cellulomonas, Cellulosimicrobium, Janibacter, Rothia, Barrentisimonas, Dietzia and Glycomyces. In antimicrobial screening, Micromonospora sp. strain GH99 and Streptomyces sp. strain GH176 were found to be potent antimicrobial strains. The metabolic extracts of these strains exhibited strong antimicrobial activity against Staphylococcus epidermidis (NCIM 2493), Shigella flexneri (NCIM 5265), Klebsiella pneumonia (NCIM 2098), and Salmonella abony (NCIM 2257). The extracts also displayed strong anti-biofilm and anticancer activities against Pseudomonas aeruginosa (NCIM 5029), Acinetobacter junii (NCIM 5188) and breast cancer cell line MCF7, respectively. Both strains also tested positive for the presence of the PKS biosynthetic gene cluster in their genomes. To effectively delineate the secondary metabolites, the extracts were subjected to MS/MS-guided molecular networking analysis. Structurally diverse compounds including the polyketides 22-dehydroxymethyl-kijanolide (GH99 strain) and Abyssomicin I (GH176 strain) were detected in the extracts. Interestingly, Brevianamide F was detected in the extract of Micromonospora, which has previously been mostly found in fungal species. Other compounds such as cyclic tripeptides, Cyclo(l-Pro-d-Ile) and Cyclo(d-Pro-l-Phe), were also identified in this strain. In summary, for the first time, we explored the diversity of Actinobacteria and evaluated their bioactive potential from the Unkeshwar hot springs. The potent strains isolated in the study could be useful in drug discovery programs.

Glycation of glucose sensitive lysine residues K36, K438 and K549 of albumin is associated with prediabetes - Rathore, R.; Sonwane, B. P.; Jagadeeshaprasad, M. G.; Kahar, S.; Santhakumari, B.; Unnikrishnan, A. G.; Kulkarni, Mahesh J. (Journal of Proteomics, 2019)
Prediabetes is a risk factor for the development of diabetes. Early diagnosis of prediabetes may prevent the onset and progression of diabetes and its associated complications. Therefore, this study aimed at the identification of novel markers for efficient prediction of prediabetes. In this pursuit, we have evaluated the ability of glycated peptides of albumin in predicting prediabetes. Glycated peptides of in vitro glycated albumin were characterized by data dependent acquisition and parallel reaction monitoring using LC-HRMS. Amongst 14 glycated peptides characterized in vitro, four peptides, particularly, FK(CML)DLGEENFK, K(AML)VPQVSTPTLVEVSR, K(CML)VPQVSTPTLVEVSR, and K(AML)QTALVELVK, corresponding to 3 glucose sensitive lysine residues K36, K438, and K549, respectively showed significantly higher abundance in prediabetes than control. Additionally, the abundance of three of these peptides, namely K(AML)QTALVELVK, K(CML)VPQVSTPTLVEVSR and FK(CML)DLGEENFK was >1.8-fold in prediabetes, which was significantly higher than the differences observed for FBG, PPG, and HbA1c. Further, the four glycated peptides showed a significant correlation with FBG, PPG, HbA1c, triglycerides, VLDL, and HDL. This study supports that glycated peptides of glucose sensitive lysine residues K36, K438 and K549 of albumin could be potentially useful markers for prediction of prediabetes. SIGNIFICANCE: Undiagnosed prediabetes may lead to diabetes and associated complications. This study reports targeted quantification of four glycated peptides particulary FK(CML)DLGEENFK, K(AML)VPQVSTPTLVEVSR, K(CML)VPQVSTPTLVEVSR, and K(AML)QTALVELVK, corresponding to 3 glucose sensitive lysine residues K36, K438 and K549 respectively by parallel reaction monitoring in healthy and prediabetic subjects. These peptides showed significantly higher abundance in prediabetes than healthy subjects, and showed significant correlation with various clinical parameters including FBG, PPG, HbA1c, and altered lipid profile. Therefore, together these four peptides constitute a panel of markers that can be useful for prediction of prediabetes.

Morphological and molecular characterization of Penicillium rubens sp.nov isolated from poultry feed - Sawant, Amol M.; Vankudoth, Ramu; Navale, Vishwambar; Kumavat, Rajkamal; Kumari, Prabla; Santhakumari, B.; Vamkudoth, Koteswara Rao (Indian Phytopathology, 2019)
Fungi are the second largest group of eukaryotic organisms, estimates ranging from 2.2 to 3.8 million and 120,000 currently accepted species. Unfortunately, identification of Penicillium species is an overwhelming task even for taxonomic experts. In the current study, we isolated identified and morphologically characterized Penicillium rubens strain NCIM-1397. Molecular characterization of P. rubens by multilocus sequence analysis (MLSA) of internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), NL (D1/D2 region) and LR (large subunit region) gene. Conversely, BenA gene differentiated P. rubens from P. chrysogenum. Moreover, Vitek MS, Matrix-assisted laser desorption ionization–time of flight mass spectrometer (MALDI-TOF–MS) failed to discriminate to strain level. Metabolic profiling of P. rubens enable to produce roquefortine C, chrysogine, meleagrine, sorbicillin and non-producers for industrially important metabolite, penicillin determined by LC–MS. Even, In addition, even molecular detection of penicillin biosynthetic pathway genes, PcbC, PenDE and Phl were negative by PCR. Nevertheless, P. rubens showed 90–100% toxicity/pathogenicity on seed germination of sorghum (Sorghum bicolor) and no further development of coleoptiles, radicle and leaf length observed. Also, it showed non-toxic to animal cell determined on Human foreskin fibroblast (HFF) cell line by In-Vitro.

Multiple-parallel-protease digestion coupled with high-resolution mass spectrometry: an approach towards comprehensive peptide mapping of therapeutic mAbs - Pradhan, Gauri; Sneha, J. M.; Sonwane, Babasaheb P.; Santhakumari, B.; Rao, Alka; Kulkarni, Mahesh J. (Journal of Proteomics, 2021)
Therapeutic monoclonal antibodies (mAbs) are structurally large and complex molecules. To be safe and efficacious, a biosimilar mAb must show high similarity to its reference product in Critical Quality Attributes (CQA). mAbs are highly sensitive to protein expression, production, manufacturing, supply chain, and storage conditions. All these factors make biosimilar mAbs intrinsically susceptible for variability during production. Accordingly, several lots of references and tests are required to establish the biosimilarity of a test mAb. The primary structure is a CQA of a mAb affecting its safety and efficacy. Here, we apply peptide mapping as an analytical method to decipher the primary structure and associated modifications for a quick quality assessment of TrastuzumAb and RituximAb innovator and biosimilar. A multiple-parallel-protease digestion strategy followed by high-resolution mass spectrometric analysis consistently achieved 100% sequence coverage along with reliable detection of post-translational modifications. Additionally, the use of supporting methods such as intact mass analysis and circular dichroism helped us to decipher the primary and higher order structures of these mAbs. We identify discernible variations in the profile of the innovator and biosimilar mAbs and validate the method for quick yet deep comparability analysis of the primary structure of biosimilar mAbs sold in the market. Significance: Peptide mapping using bottom-up approach is one of the most common methods for the characterization of therapeutic monoclonal antibodies. Herein, we describe a multi-parallel-protease digestion strategy using a combination of five different proteases followed by high-resolution mass spectrometric analysis with TrastuzumAb and RituximAb as an example. This resulted in a comprehensive identification of peptides with increased reliability and identification of different PTMs. Additional supporting orthogonal methods like intact mass and higher-order structure analysis helped evaluate broader conformational properties.
Keywords: LC-MS/MS; PTM; RituximAb; Therapeutic monoclonal antibodies; TrastuzumAb

Rhamonolipids produced by Pseudomonas aeruginosa promotes methane hydrates formation in fixed bed silica gel medium - Arora, Amit; Cameotra, Swaranjit Singh; Balomajumder, Chandrajit; Kumar, Rajnish; Singh, Anil Kumar; Santhakumari, B.; Kumar, Pushpendra; Laik, Sukumar (Marine Geophysical Research, 2021)
Natural gas hydrates are seen as an alternative future energy source. They have also been valued for their carbon dioxide capturing capability, gas separation, desalination, natural gas storage and transportation. Developing economical and viable gas hydrate based technology is one of the most promising research areas of present decade. Successful commercialization of gas hydrate based technology is often curtailed due to slow formation rate. The present study evaluates biosurfactant as a kinetic promoter of methane hydrates formation in a fixed bed C type silica gel medium. Biosurfactant was produced by growing Pseudomonas aeruginosa strain A11 in glycerol supplemented mineral salt medium. Biosurfactant characterization with FTIR, NMR and MALDI-TOF spectroscopy reveled it to be a glycolipids type biosurfactant namely rhamnolipids. Saturating C type silica gel with of 100 ppm rhamnolipids solution enhanced the rate of methane hydrates formation by reducing the induction time. Mole of methane consumed and percentage of water to hydrate conversion was observed to be more in 1000 ppm rhamnolipids saturated C type silica gel as compared to quiescent water system and water saturated silica gel system. Overall results suggest that rhamonolipids produced by strain A11 in combination with silica gel can be utilized as environmentally safe kinetic promoter for methane hydrate formation.
Keywords: Biosurfactant; Energy; Glycolipids; Induction time; Kinetic promoter

SWATH-MS reveals that bisphenol A and its analogs regulate pathways leading to disruption in insulin signaling and fatty acid metabolism - Kulsange, Shabda E.; Sharma, Monika; Sonawane, Babasaheb; Jaiswal, Meera R.; Kulkarni, Mahesh J.; Santhakumari, B. (Food and Chemical Toxicology, 2024)
Bisphenol A (BPA) is an endocrine-disrupting chemical (EDC), associated with obesity and insulin resistance. The FDA prohibited the use of BPA-based polycarbonate resins in infant formula packaging; thus, its analogs, viz. Bisphenol S (BPS) and Bisphenol F (BPF) were considered alternatives in epoxy resins, plastics, and food cans. As these analogs might evoke a similar response, we investigated the role of Bisphenols (BPA, BPF, and BPS), on insulin signaling in CHO-HIRc-myc-GLUT4eGFP cells at environmentally relevant concentrations of 2 nM and 200 nM. Insulin signaling demonstrated that Bisphenols reduced phosphorylation of IR and AKT2, GLUT4 translocation, and glucose uptake. This was accompanied by increased oxidative stress. Furthermore, SWATHMS-based proteomics of 3T3-L1 cells demonstrated that Bisphenol-treated cells regulate proteins in insulin resistance, adipogenesis, and fatty acid metabolism pathways differently. All three Bisphenols induced differentially expressed proteins enriched similar pathways, although their abundance differed for each Bisphenol. This might be due to their varying toxicity level, structural differences, and estrogen-mimetic activity. This study has important implications in addressing health concerns related to EDCs. Given that the analogs of BPA are considered alternatives to BPA, the findings of this study suggest they are equally potent in altering fatty acid metabolism and inducing insulin resistance.
Keywords: Bisphenols; Estrogen; Lipid droplet; Mitochondrial beta-oxidation; Oxidative stress; PPAR gamma

Yoga therapy attenuates the progression of diabetes - insights from proteomics and metabolomics analysis - Sonwane, Babasaheb P.; Raut, Pooja; Chitalkar, Jyotsna; Godbole, Smita; Sabnis, Shanta; Gupta, Jyoti; Santhakumari, B.; Deshpande, Mukund V.; Kulkarni, Mahesh J. (International Journal of Yoga, 2024)
<p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Objective: Diabetes management remains challenging despite advancements in therapeutics, with many subjects developing complications. Yoga has been shown to aid diabetes management. This study investigates the impact of yoga therapy on diabetes progression, utilizing proteomics and metabolomics analyses to explore underlying molecular mechanisms. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Methodology: A 3-month longitudinal study involving healthy subjects with prediabetes and diabetes was conducted. Blood glucose, glycated hemoglobin (HbA1c), lipid profile, and malondialdehyde (MDA) levels were measured before and after the yoga intervention. <p style="box-sizing: inherit; line-height: 1.5; margin: 1.2rem 0px; color: rgb(33, 33, 33); font-family: BlinkMacSystemFont, -apple-system, "Segoe UI", Roboto, Oxygen, Ubuntu, Cantarell, "Fira Sans", "Droid Sans", "Helvetica Neue", sans-serif; font-size: 16px;"> Results and conclusion: Healthy subjects showed no significant changes in blood glucose, lipid profile, HbA1c, or MDA levels. However, subjects with prediabetes and diabetes experienced positive changes, with decreases in HbA1c and MDA levels. Proteomics and metabolomics analyses provided insights into the molecular mechanisms by which yoga attenuates diabetes progression in subjects with prediabetes and diabetes. This study is a pioneering effort to understand the molecular basis of yoga's beneficial effects on diabetes management.